LEGAL SYSTEM OF SCANDINAVIAN COUNTRIES - Z. K. Ayupova; D. U. Kussainov; Winston Nagan (Scientific Journal of Pedagogy and Economics, 2019)
The article presents a General description of the legal systems of the Scandinavian countries. The authors come to the conclusion that the common historical roots, the closest political, economic and cultural ties predetermined the existence of similar features in the legal systems of these States. At the same time, the Scandinavian legal systems have features typical of the Anglo-Saxon and Romano-German legal families. Legal systems in Scandinavian countries are divided into two groups. The first includes Denmark, Norway and Iceland, the right of which historically evolved on the basis of almost identical in their content compilations Danish and Norwegian law, implemented in the second half of the XVII century the second group includes Sweden and Finland. The analysis of modern legal systems of Scandinavian countries shows some commonality of Scandinavian and Romano-German law. First of all, it is manifested in the similarity of sources of legal regulation. In the Scandinavian countries, the law is the main source of law, and the courts formally cannot, by resolving a particular dispute, create legal norms. This is the most significant difference between the Nordic and common law.